Utilizing an integrated tri-layered scaffold with Titanium-Mesh-Cage base to repair cartilage defects of knee in goat model. (August 2020) - Zhai, Chenjun; Zuo, Qiang; Shen, Kai; Zhou, Jinchun; Chen, Jun; Zhang, Xiao; Luo, Chunyang; Fei, Hao; Fan, Weimin
Abstract: The application of multilayered monolithic scaffolds to repair osteochondral defects has become a hot research topic due to the advantage of simulating native osteochondral physiological structure. However, it was difficult to promote proliferation and migration of different kinds of cells in the corresponding layers under the same culture condition. Besides, the methods utilized in previous researches to construct tissue-engineered osteochondral construct were time-consuming, laborious, complicated, costly and difficult to ensure the quality and integration of multilayered construction. Inspired by the application of titanium mesh cage (TMC) for bone graft in spinal fusion surgery, we attempt to 3D print an integrated tri-layered scaffold with Titanium-Mesh-Cage base which could be filled with autogenous cancellous bone for bone graft to the osteochondral defect. Finally, the results of repairing cartilage defects of knee with this scaffold in goat model were evaluated. The results of in-vivo experiments suggested that utilizing the integrated tri-layered scaffold with Titanium-Mesh-Cage base to repair osteochondral defect was a convenient, cost-effective and time-saving procedures, which could achieve a satisfactory repair result as good as that of Mosaicplasty. Graphical abstract: Unlabelled Image Highlights: The design of cage-like structure allows autogenous cancellous bone graft to osteochondral defects. This design could simplify the procedure of constructing engineered complex tissue. Autologous cancellous bone graft in Titanium-Mesh-Cage base could promote cartilage regeneration on the upper layers.